Recurrent Laryngeal Nerve in Thyroid Surgery: Is Routine Identification necessary? - Jahangir Sarwar Khan , Kamran Malik , Zeeshan Hussain Khawaja , Hamid Hassan , Mohammad Iqbal, Jahangir Sarwar Khan , Kamran Malik , Zeeshan Hussain Khawaja , Hamid Hassan , Mohammad Iqbal (Journal of Rawalpindi Medical College, 2008)
Background: To assess the risk of recurrent laryngeal nerve palsy (RLNP) after thyroidectomy with and without routine identification of the recurrent laryngeal nerve (RLN) during the operation. Methods: This quasi experimental trial was conducted in Surgical Department of Rawalpindi General Hospital from Jan 2005 – Dec 2006 One hundred patients who underwent subtotal thyroidectomy, were included in the study. There were 50 patients in each group (group A and group B), with and without routine identification of the recurrent laryngeal nerve (RLN) during the operation. Both groups were prospectively analyzed comparing post operative hoarseness. Result: The mean age in Group A was 34.06 yrs S.D±7.55 and in Group B 31.8years S.D±7.54. In Group A 46(92%) were females while Group B 48(96%) were females. Incidence of postoperative hoarseness occurred in 4 % in both groups. 8 patients developed post operative RLN palsy. Complete recovery of RLN function was documented in all patients within 3 months of surgery. Recovery from temporary RLNP ranged from 3 days to 3 months (mean 4±2.5weeks). Overall incidence of temporary and permanent RLNP was 4.0% and 0%, respectively in both groups. Conclusion: Though there is no significant risk of hoarseness with or without routine identification of RLN, surgeons should be aware of the variations and have a thorough knowledge of normal anatomy of RLN, in order to achieve a high standard of care. This will ensure the integrity and safety of the RLN in thyroid surgery